The Implementation of Hydroponics as an Alternative Agricultural System in Sukamakmur Village, Ciomas District, Bogor Regency - Nurul Nisa'a Amin; Dewi Juliah Ratnaningsih; Pepi Rospina Pertiwi; Ulul Hidayah; Ariyanti Hartari; Restu Para Ratu; Intan Oktaviani (Wikrama Parahita : Jurnal Pengabdian Masyarakat, 2026)
Hydroponic cultivation has emerged as a strategic approach in community empowerment initiatives, particularly in contexts characterized by limited land availability, declining soil fertility, and constrained access to conventional agricultural practices. This study aimed to evaluate the effectiveness of a hydroponic training program in enhancing participants’ knowledge and readiness to adopt soilless cultivation techniques. A pretest and posttest design was employed to assess ten indicators encompassing fundamental hydroponic concepts, system typologies, nutrient management, and critical plant growth parameters. The findings revealed substantial improvements in participants’ knowledge, as evidenced by markedly higher post-test scores across all indicators. Significant gains were observed in participants’ understanding of suitable crop selection, optimal pH regulation, nutrient solution management, and the appropriate use of measurement instruments. Importantly, these enhanced competencies were translated into practical implementation, with participants, particularly members of the PKK group, successfully establishing hydroponic systems, conducting harvesting activities, and commercializing their produce through local bazaars. This outcome underscores the program’s tangible contribution to small-scale food production and the generation of supplementary household income. Taken together, the study demonstrates that structured and practice-oriented hydroponic training effectively strengthens technical capacity while fostering community empowerment and sustainable livelihood development